Improvements of electrical and thermal characteristics for AlGaN/GaN HEMT grown by metal-organic chemical vapor deposition on silicon-on-insulator (SOI) substrate. (1st July 2022) - Hieu, Le Trung; Chiang, Chung-Han; Anandan, Deepak; Dee, Chang-Fu; Hamzah, Azrul Azlan; Lee, Ching-Ting; Lin, Chung-Hsiung; Chang, Edward Yi
Abstract: AlGaN/GaN high electron mobility transistors (HEMTs) heterostructures are grown by metal-organic chemical vapor deposition on silicon-on-insulator (SOI) substrate and high-resistivity silicon (HR-Si) simultaneously to investigate the influence of substrate types on electrical and thermal characteristics. The AlGaN/GaN HEMT epitaxial structure grown on SOI achieved high electron mobility (1900 ± 19 cm 2 (V s) −1 ) and high two-dimensional electron gas carrier concentration (9.1 ± 0.1 × 10 12 cm −2 ). The GaN HEMT metal–insulator–semiconductor gate device fabricated on the structure grown on the SOI substrate exhibits higher saturation current and improved buffer breakdown voltage compared with devices fabricated on HR-Si substrate. In particular, SOI substrate helps to improve the thermal-sensitive strain of the GaN-based heterostructure and reduced defect density in the epitaxy, thereby improve the temperature-dependent on-resistance ( R ON ) and the dynamic R ON of the device.